A Stress Orientation Analysis Framework for Dislocation Glide in Face-Centred Cubic Metals - Fernando Daniel León-Cázares; Catherine Mary Fiona Rae (Crystals, 2020)
Plastic deformation in metals is heavily influenced by the loading direction. Studies have explored its effects on multiple mechanisms by analysing individual dislocations, but there is currently no systematic way of rationalising the cooperative behaviour of the different slip systems for arbitrary stress tensors. The current study constitutes the foundation of a new orientation analysis framework for face-centred cubic crystals by introducing “stress orientation maps”, graphical tools to simultaneously analyse the effects of loading orientation on the stress state of the <semantics> a 2 〈 1 <mover> 1 ¯ </mover> 0 〉 { 111 } </semantics> and <semantics> a 6 〈 112 〉 { 111 } </semantics> slip systems in a comprehensive, yet intuitive way. Relationships between the Schmid and Escaig stresses are described from geometrical constraints of the slip systems in the crystal structure, linking the dislocation behaviour on a slip plane with the stress tensor via a one parameter description. The case of uniaxial loading along different orientations within the fundamental sector of the unit cell is explored to describe the physical basis, properties and capabilities of this framework. The stress normal to the slip plane is then considered in the analysis via an extension of the Mohr’s circles. The orientation dependence of two twin nucleation mechanisms from the literature are examined as examples of how the stress orientation maps can be used.